Large variation in Mekong river plastic transport between wet and dry season - van Emmerik, Tim H. M.; Schreyers, Louise J.; Mellink, Yvette A. M.; Sok, Ty; Arias, Mauricio E. (Frontiers in Environmental Science, 2023)
Rivers act both as pathways for land-based plastic waste into the ocean, and as reservoirs for long-term plastic retention. Reliable observations are key to designing and evaluating strategies to prevent and reduce plastic pollution. Several measurement methods have been developed to quantify macroplastic ($>$0.5 cm) storage and transport in rivers. Method harmonization is crucial to ensure consistency in the data collected using different techniques, allowing comparative analysis of plastic pollution within and between rivers. In this paper, we harmonized data collected using two different methods to estimate the floating plastic item and mass transport in the wet and dry season for the Mekong-Tonlé Sap-Bassac river system around the city of Phnom Penh, Cambodia. During the wet season, plastic transport in the Mekong increased with a factor of up to 170 (item transport) and 294 (mass transport) compared to the dry season. The river plastic mass balance around Phnom Penh changed considerably due to the flow reversal of Tonlé Sap river between the wet and dry season. Downstream of Phnom Penh, the total plastic transport was consistently higher than upstream, emphasizing its role as entry point of plastic pollution into the Mekong. The largest sources of uncertainty are assumed to be caused by varying size ranges, extrapolation from observation point to full river width, and the contribution of submerged plastic to the total transport. Our results show that river plastic transport dynamics are highly variable over time and space, especially around confluences, bifurcations and urban areas.